Software developments failures : anatomy of abandoned projects. - Ewusi-Mensah, Kweku, ....- (Cambridge : MIT, 2003)
Failed or abandoned software development projects cost the US economy alone billions of dollars a year. In this text, Kweku Ewusi-Mensah offers an empirically grounded study that suggests why these failures happen and how they can be avoided.
Keywords: Software-ontwikkeling.